Kematangan emosi dengan penyesuaian pernikahan pada pelaku perkawinan usia dini - Suyanti, Suyanti (PSYCOMEDIA : Jurnal Psikologi, 2023)
This research aims to determine the relationship between emotional maturity and marital adjustment in couples who marry at an early age. Participants in this research were women in early marriage who had been married for more than 3 years in Kendit. The sampling technique used in this research is non-probability sampling using incidental sampling. The analysis of this research data used the Spearman rho correlation test. The results of the correlation test show that there is a positive and significant correlation between emotional maturity and marital adjustment in 34 couples who married at an early age. These results can be interpreted as meaning that the higher an individual's emotional maturity, the higher the marital adjustments they will make.